Pengintegrasian data extensible markup language (XML) ke dalam pangkalan data hubungan menggunakan common warehouse metamodel (CWM) - Mohd. Nasir, Wan Mohd. Haffiz (2007)
The demand for rapid data integration is getting higher as more and more information sources appear in modern enterprises. Extensible Mark-up Language (XML) is fast becoming the new standard for data representation and exchange on the World Wide Web, e.g., in B2B e-commerce, making it necessary for data analysis tools to handle XML data as well as traditional data formats. The purpose of this research is to enhance the technique for XML data integration into relational data to solve integration problems such as missing data. The method that had been proposed is to apply Common Warehouse Metamodel (CWM) for metadata interchange and metadata management that incorporates a common shared metamodel for metadata syntax and semantics. The results of this research are the enhancement of the integration architecture and approach by applying CWM as well as the development of an interface software to simplify the integration process as a solution for the missing data problem.